A Study on the Mediating Effect of Knowledge Management Capability between HRM Practices and Radical Innovation Capability in Malaysia SME-ICT - Mohd Yusof, Ahmad Nizam; Dzulkalnie, Natasha; Mohd Shukor, Shamsul Azreen; Sumardi, Nur Athirah; Kamarulzaman, Maliza Delima (Advances in Social Sciences Research Journal, 2024)
Increasingly, executives understand the value of information as a source of new ideas for their companies. Only a small number of research examine the role of HR management in increasing knowledge competency, which leads to enhanced creativity inside firms. Because of this, this research examines how human resource management policies and practices affect the link between knowledge management competency and innovation. Consequently, The research is based on primary data collected from 200 SMEs in Malaysia’s Klang Valley in the ICT sector. The study’s goals necessitate a quantitative methodology. ICT small and medium-sized enterprises (SMEs) owners, CEOs, and managers are surveyed utilizing a survey method. More than 200 responses were received and analysed in the course of this study. The study models and hypotheses were evaluated using the Partial Least Squares (PLS) method. Research is scarce in the domains of HRM and innovation, as well as the interaction between HRM and knowledge management in the context of innovation. Research indicates a good correlation between Human Resource Management (HRM) Capabilities and Knowledge Management.